Agronomic, economic, and environmental performance of nitrogen rates and source in Bangladesh’s coastal rice agroecosystems - Emran, Shah-Al; Krupnik, Timothy J.; Kumar, Virender; Ali, M. Yusuf; Pittelkow, Cameron M. (Elsevier, 2019)
Farmers in low-elevation coastal zones in South Asia face numerous food security and environmental sustainability challenges. This study evaluated the effects of nitrogen (N) rate and source on the agronomic, economic, and environmental performance of transplanted and rainfed ‘aman’ (monsoon-season) rice in Bangladesh’s non-saline coastal areas. Fifty-one farmers participated in trials distributed across two landscape positions described as ‘highlands’ (on which field water inundation depth typically remains <30 cm) and ‘medium-highlands’ (inundation depths 30–90 cm) planted singly with varieties appropriate to each position (BRRI dhan 39 for highlands and the traditional variety Bhushiara for lowlands). Researcher designed but farmer-managed dispersed plots were located across three district sub-units (Barisal Sadar, Hizla, Mehendigonj) and compared N source (broadcast prilled urea or deep-placed urea super granules (USG)) at four N rates. Rice grown on medium-highlands did not respond to increasing N rates beyond 28 kg N ha−1, indicating that little fertilization is required to maintain yields and profitability while limiting environmental externalities. In highland locations, clear trade-offs between agronomic and environmental goals were observed. To increase yields and profits for BRRI dhan 39, 50 or 75 kg N ha−1 was often needed, although these rates were associated with declining energy and increasing greenhouse gas (GHG) efficiencies. Compared to prilled urea, USG had no impact on yield, economic, energy and GHG efficiencies in medium-highland locations. USG conversely led to 4.2–5.8% yield improvements at higher N rates on highlands, while also increasing energy efficiency. Given the observed yield, agronomic and economic benefit of USG, our preliminary results that farmers can consider use of USG at 50 kg N ha−1 to produce yields equivalent to 75 kg N ha−1 of prilled urea in highland landscapes, while also reducing environmental externalities. These results suggest that when assessing sustainable intensification (SI) strategies for rice in South Asia’s coastal zones, N requirements should be evaluated within specific production contexts (e.g. cultivar type within landscape position) to identify options for increasing yields without negatively influencing environmental and economic indicators. Similar studies in other parts of coastal South Asia could help policy-makers prioritize investments in agriculture with the aim of improving rice productivity while also considering income generation and environmental outcomes